Gastroprotective effects of oral nucleotide administration. Issue 2 (9th August 2005) - Belo, A; Marchbank, T; Fitzgerald, A; Ghosh, S; Playford, R J
Abstract : Background and aims: Nucleotides form the building blocks of DNA and are marketed as dietary supplements, alone or in combination with other ingredients, to promote general health. However, there has been only limited scientific study regarding the true biological activity of orally administered nucleotides. We therefore tested their efficacy in a variety of models of epithelial injury and repair. Methods: Effects on proliferation ([ 3 H] thymidine incorporation) and restitution (cell migration of wounded monolayers) were analysed using HT29 and IEC6 cells. The ability of a nucleotide mixture to influence gastric injury when administered orally and subcutaneously was analysed using a rat indomethacin (20 mg/kg) restraint model. Results: In both cell lines, cell migration was increased by approximately twofold when added at 1 mg/ml (p<0.01); synergistic responses were seen when a mixture of nucleotides was used. Cell proliferation was stimulated by adenosine monophosphate (AMP) in HT29, but not in IEC6, cells. Gastric injury was reduced by approximately 60% when gavaged at 4–16 mg/ml (p<0.05), concentrations similar to those likely to be found in consumers taking nucleotide supplements. Systemic administration of nucleotides was unhelpful. Conclusions: Nucleotides possess biological activity when analysed in a variety of models of injury and repair and could provide a novel inexpensive approach for the prevention and treatment of the injurious effects of non steroidal anti-inflammatory drugs and other ulcerative conditions of the bowel. Further studies on their potential benefits (and risks) appear justified.